Optimum temperature and state of maturity for storing persimmons, diospyrus kaki L., (caquí 'giombo') - Vieites, Rogério L. [UNESP]; Picanço, Nagela F.M. [UNESP]; Daiuto, Érica R. [UNESP]; Moraes, Maria R. [UNESP] (Bentham Science Publishers, 2012)
Persimmons have a short harvest season, making it necessary to use adequate storage techniques to extend their shelf life. The objective of this work was to find the best time to harvest the fruit and the best storage temperature for the persimmon, caquí 'giombo'. The fruits were harvested in four different stages of maturity: 1 - totally green; 2 - start of maturity 75% green; 3 - medium maturity 50% green; 4 - mature 25% green. The fruits were stored 35 days at 0, 3 and 6 oC and 85±5% relative humidity. The following analyses were done every seven days: respiratory activity, weight loss, soluble solids, titratable acidity and ascorbic acid content. The weight loss was less in the advanced maturity states and lower storage temperature. The production of CO2 oscillated during the experimental period for all four maturity states. More CO2 was produced by the most mature fruits. The soluble solids content varied little during the experiment and was greatest for the most mature fruits. The ascorbic acid content increased throughout the 35 days for all maturity states. They were highest in the most mature fruits. © 2012 Bentham Science Publishers.
Keywords: Ascorbic acid; Diospyrus kaki l.; Refrigeration; Storage